2019
DOI: 10.1071/rd19260
|View full text |Cite
|
Sign up to set email alerts
|

Equine non-invasive time-lapse imaging and blastocyst development

Abstract: In this study we examined the timeline of mitotic events of invitro-produced equine embryos that progressed to blastocyst stage using non-invasive time-lapse microscopy (TLM). Intracytoplasmic sperm injection (ICSI) embryos were cultured using a self-contained imaging incubator system (Miri®TL; Esco Technologies) that captured brightfield images at 5-min intervals that were then generated into video for retrospective analysis. For all embryos that progressed to the blastocyst stage, the initial event of extrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It has been suggested that the osmotic pressure, gap junctions in between TE and inner cell mass (ICM), ion and water channels and pumps, and contractile proteins are involved in this event [6][7][8][9] . Previously, our laboratory reported embryo pulsing being observed in in vitro -produced equine embryos [10] . Similarly, Lewis et al, reported the presence of pulsing in equine embryos using timelapse imaging [11] .…”
Section: Introductionmentioning
confidence: 93%
“…It has been suggested that the osmotic pressure, gap junctions in between TE and inner cell mass (ICM), ion and water channels and pumps, and contractile proteins are involved in this event [6][7][8][9] . Previously, our laboratory reported embryo pulsing being observed in in vitro -produced equine embryos [10] . Similarly, Lewis et al, reported the presence of pulsing in equine embryos using timelapse imaging [11] .…”
Section: Introductionmentioning
confidence: 93%
“…Both CO 2 and tri-gas box incubators were initially purchased for oocyte maturation and culture respectively. Benchtop incubators have since been obtained for culturing embryos; these incubators have grown in ubiquity and appear to provide superior performance relative to traditional box incubators (Gelo et al, 2019;Martino et al, 2019;Meyers et al, 2019). Also purchased was a biosafety Given the many moving parts involved in starting the laboratory, media preparation proved to be a time-consuming and mistake-laden task, especially when a designated technician was not available.…”
Section: Do Not Purchase Cheap Equipmentmentioning
confidence: 99%
“…In humans, in recent years, many tools have been developed to assist medical teams in this selection, while in horses, the quality assessment of cultured embryos is at its beginning. Methods can be invasive, such as embryo biopsy for pre-implantation genetic testing [ 124 , 157 , 158 ], or non-invasive, such as embryo monitoring by time-lapse imaging [ 159 , 160 , 161 , 162 , 163 ], metabolomics, or aneuploidy diagnosis on spent culture media (niPGT–A) [ 164 ]. These different techniques present different sensitivities, specificities, and acceptability, but have allowed to better control early embryonic development, to refine the criteria for the choice of the embryo to be transferred, and to promote single embryo transfer and thus considerably reduce the risks of multiple pregnancies (see below).…”
Section: Comparison Of Assisted Reproduction Techniques In Horses and Humansmentioning
confidence: 99%